Evaluating the Impact of VevoVitall and/or CRINA as Potential Porcine Epidemic Diarrhea Virus Mitigation Strategies as Determined by Polymerase Chain Reaction Analysis and Bioassay - J. T. Gebhardt; J. C. Woodworth; C. K. Jones; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; R. A. Cochrane; C. R. Stark; J. Bergstrom; Phillip Charles Gauger; J. Bai; Qi Chen; et al. (Kansas Agricultural Experiment Station Research Reports, 2016)
Feed and feed ingredients have been shown to be potential vectors of porcine epidemic diarrhea virus (PEDV). Potential strategies to mitigate the risk of disease transmission via feed and feed ingredients would be valuable to the swine and feed milling industries. Therefore, the objective of this experiment was to determine the impact of VevoVitall (5,000 ppm; DSM Nutritional Products Inc., Parsipanny, NJ), CRINA (200 ppm; DSM Nutritional Products Inc., Parsipanny, NJ), and a combination of both products (COMBINATION; 5,000 ppm VevoVitall and 200 ppm CRINA) as feed additives with potential to mitigate the risk of PEDV, in swine gestation diet (FEED) and spraydried porcine plasma (SDPP) as determined by real time quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) analyzed at seven sampling days post laboratory inoculation (d 0, 1, 3, 7, 14, 21, and 42) and bioassay. There was a marginally significant treatment × feed matrix × day interaction (P = 0.082), in which the cycle threshold (Ct) value increased over time in the diet when treated with the COMBINATION, whereas, there was no increase over time observed in SDPP. There was a highly significant (P<0.001) feed matrix × day interaction in which the Ct increased over time in FEED, whereas, there was very little increase over time observed in SDPP. Additionally, there was a marginally significant treatment × feed matrix interaction (P = 0.079). Overall, the COMBINATION was most effective at reducing the quantity of genetic material as detected by qRT-PCR (P<0.001). Virus shedding was observed in the d 7 post-inoculation SDPP COMBINATION treatment, as well as d 0 FEED COMBINATION treatment. No other treatment bioassay room had detectable RNA shed and detected in fecal swabs or cecal contents (d 1, 3, 7, 14, and 21 post-laboratory inoculation FEED, COMBINATION). In summary, the combination of CRINA and VevoVitall enhanced degradation of PEDV RNA in swine feed, but had no impact on RNA degradation in SDPP. Furthermore, both untreated feed and feed treated with the combination of CRINA and VevoVitall caused infection at d 0 post-laboratory inoculation; however, neither set of samples was infective at d 1 post-laboratory inoculation.
Keywords: feed additive; feed matrix; PEDV; swine